Environmental criminology : spatial analysis and regional issues - Leonard, Liam (Advances in sustainability and environmental justice, 2017)
Environmental Criminology: Spatial Analysis and Regional Issues combines various academic perspectives to provide a multi-disciplinary approach to examining environmental criminology. Using sociological, criminological, anthropological, historical and media analysis, this volume examines local and regional issues in crime. The interdisciplinary nature of the collection makes the book ideal for students or researchers who wish to expand their approach to environmental criminology.